2015
DOI: 10.4028/www.scientific.net/kem.658.36
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Liquation in Ni-Base Superalloy by Using Confocal Laser Scanning Microscopy

Abstract: In-Situ direct observation was used to observe the liquation in an Inconel 617. High-Temperature Confocal Laser Scanning Microscopy (HT-CLSM) was used to observe the phenomena. Experiment was perform at 1330 °C with heating rate 5 °C/s. Results showed that the liquidation started at 1319.2 °C (268.08 seconds) in which liquid formed around precipitate. At 1330.5 °C (272.05 seconds) the liquid film wet and penetrated along grain boundaries. Then after 277.05 seconds, sufficient liquid film formed and moved freel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Wen [3] reported the behavior of grain boundary liquation cracking in fiber laser welding of alloy 617 and found that the degree of liquation cracking decreased when the heating input and preheating temperature increased. Phuraya [22] used a high-temperature confocal laser scanning microscopy to investigate the liquation process of alloy 617 by in situ observation. Meanwhile, Xu [23] reported that some lamellar structures occurred near the fusion line of alloy 617B welded joint and found that the peak temperature played a key role in the formation of these lamellar structures.…”
Section: Introductionmentioning
confidence: 99%
“…Wen [3] reported the behavior of grain boundary liquation cracking in fiber laser welding of alloy 617 and found that the degree of liquation cracking decreased when the heating input and preheating temperature increased. Phuraya [22] used a high-temperature confocal laser scanning microscopy to investigate the liquation process of alloy 617 by in situ observation. Meanwhile, Xu [23] reported that some lamellar structures occurred near the fusion line of alloy 617B welded joint and found that the peak temperature played a key role in the formation of these lamellar structures.…”
Section: Introductionmentioning
confidence: 99%
“…At an LMP value of 28,000, the aged specimen resisted load bearing better than the AS and SO specimens. This was because the aged specimens had more γ'-Ni3 (Al, Ti) precipitate, which resulted in high temperature strength and creep strength [12][13].…”
Section: Fig 4 Larson-miller Parameter Plot For Inconel 617 In As-rementioning
confidence: 99%